Stability analysis of associative memory network composed of stochastic neurons and dynamic synapses - Katori, Yuichi; Otsubo, Yosuke; Okada, Masato; Aihara, Kazuyuki (Frontiers in Computational Neuroscience, 2013)
We investigate the dynamical properties of an associative memory network consisting of stochastic neurons and dynamic synapses that show short-term depression and facilitation. In the stochastic neuron model used in this study, the eﬃcacy of the synaptic transmission changes according to the short-term depression or facilitation mechanism. We derive a macroscopic mean ﬁeld model that captures the overall dynamical properties of the stochastic model. We analyze the stability and bifurcation structure of the mean ﬁeld model, and show the dependence of the memory retrieval performance on the noise intensity and parameters that determine the properties of the dynamic synapses, i.e., time constants for depressing and facilitating processes. The associative memory network exhibits a variety of dynamical states, including the memory and pseudo-memory states, as well as oscillatory states among memory patterns. This study provides comprehensive insight into the dynamical properties of the associative memory network with dynamic synapses.